STRATEGI PENGUATAN DAYA SAING USAHA KECIL DAN MENENGAH (UKM) BATIK MENGHADAPI ASEAN ECONOMIC COMMUNITY (AEC) - Siti Nurhayati (Fakultas Ekonomi Universitas Pekalongan, 2017)
This research is inspiring by the fact that Indonesian batik become to shifting market. Those shift cause of the circulation printing textile with batik motive both domestic and abroad come veryfaster. On the other side, Indonesia become as member of the ASEAN Economic Community (AEC), that have the consequentcies is all of products and services must compete with all Asean statemembers, so do the batik product. The research concentrated on the centres of Indonesian batik, includes Pekalongan, Surakarta, Yogyakarta, and Bantul. The sample determinate with non probability sampling and than elected 8 companies of batik, that include on Small and Medium Enterprises (SME) , the test of data validity use the triangulasi technique. The result of this research show that UKM batik must preparing some strategies to compete with another state members of ASEAN Economic Community (AEC). Those strategies would be conductto the mayor strategy namely the competitive power strategy.Key words : ASEAN Economic Community (AEC), Small and Medium Enterprise (SME), batik, competitive power strategy